Engaging children in lessons: the role of eﬃcient andeﬀective teachers - López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (Taylor & Francis, 2017)
The training of eﬀective teachers has been one of the main aims ofeducational systems, in so far as it could be an important tool toimprove the education performance of children and, consequently,contribute to their career progression and foster social mobilitytowards a more meritocratic society. The present study intends toidentify these teachers by their ability to engage young students inlessons, which may reﬂect the capacity of their teaching practicesand eﬃcient use of available resources to increase students’ learning.We focus on 4th-grade reading and mathematics teachers in Spain –using TIMSS and PIRLS 2011 data – and we propose a 2-step proce-dure for this analysis: the 1st step obtains teachers’ eﬃciency scores,which are later employed in a 2nd step – together with teachers’practices – to explain children’s engagement in lessons.
https://openpolicyfinder.jisc.ac.uk/id/publication/6043
Keywords: Profesores - Formación profesional; Rendimiento académico - Modelos matemáticos; Movilidad social; Eficacia en la enseñanza; Children engagement; Teachers' efffectiveness; Teachers' efficiency; Time-invariant stochastic frontier analysis; Multilevel regression analysis